The Three Faces of America and the Problem of Assimilation in the Huntington’s Paradigm - Nedeljković, Zoran (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
In this paper, the author offers an interpretation of Huntington’s account of three possible faces of America, the socio-political state of America in the immediate future. He derived these three perspectives from his paradigm of the clash of civilizations. These three faces of America are: 1. America as an open society to the rest of the world; 2. Imperial America, in which the world would be transformed into America; 3. America remains America, as opposed to spreading a new wave of ideas through the media about multiculturalism as the most humane way of existence of culturally diverse population in the human community. Between these three choices, Huntington opts for the third option, because only if America remains America can the national identity be preserved on the foundations of Anglo-Protestant culture. Immigrant assimilation is the key to solving the problem for the survival of the United States. In this text, the author discusses Huntington’s three interpretations of the concept of assimilation and comes to the conclusion that through the concept of a foreigner, the other, who moves away from the domicile population like a quasar, as an embodiment of human alienation, all three possible imaginary histories of America are broken